Carbapenemase-producing Enterobacteriaceae (CPE) patient notification exercise. (13th November 2019) - Murphy, L; Tysall, L; Wellington, L; Guthrie, L; Inverarity, D; Willocks, L; Czarniak, E; McCallum, A; Gillies, T
Abstract: Issue: CPE has become endemic in many European countries. Scotland has few locally acquired cases at present and interventions are aimed at minimising transmission of CPE into acute hospital settings. Description of the problem: NHS Lothian held an incident management team (IMT) following the transmission of CPE in an inpatient setting. Initial management of the incident included informing and screening all inpatient contacts, enhanced infection control precautions and staff education. The IMT considered whether to inform and screen patient contacts who had been discharged. A literature review was carried out and teams in the UK who had considered patient notification exercises for CPE were contacted. This highlighted variation in approach. The IMT assessed whether a patient notification exercise was required and considered: The need to reduce the risk of CPE transmission in acute hospitals by screening and isolating community contacts on readmission to hospital. The ethics of raising patient anxiety around CPE transmission with limited options for effective treatment. Risk stratification to identify contacts at highest risk. Information Governance: electronic tagging of case notes if patients have not been informed. Results: The IMT agreed that a patient notification was appropriate. Contacts were risk assessed to determine those at greatest risk of CPE transmission. After speaking to GPs, 33 patients were sent letters. No screening of community contacts was advised unless they were re-admitted to an acute hospital or resided in a care facility. No further CPE reports have been linked to the situation. Lessons: The IMT worked through the issues systematically to protect the public's health without infringing their rights. The IMT advised that the Scottish CPE toolkit should be revised to support future Incidents including how to analyse transmission pathways, undertake patient notification exercises and meet public health ethics standards. Key messages: There needs to be clear guidance on how to manage contacts of patients with CPE once discharged from hospital. Team work between Public health and Infection control is essential in manageing incidents of CPE in hospitals.